(untitled) (Journal of Oriental Studies, 2025)
Contemporary Turkey’s foreign and domestic, educational, propaganda policy, as well as official rhetoric, prove that the synthesis of Islam and nationalism has turned into the country’s state identity. In 1923-founded Turkey, the competition between secularism and religiosity has a history of decades and at some point, nationalism was more openly intertwined with Islamic ideology, and today it is essentially one whole. In turn, Islamism and nationalism in Turkey, developing in parallel from the second half of the last century, had phases of competition, but often there were obvious preconditions for their merging or at least close cooperation. Some reflections of this phenomenon can be seen in the programs of pro-Islamic parties operating since the 1970s. In this article, the programs of the "National Order", "National Salvation" and "Welfare" parties are examined, presenting certain definitions of nationalism in them, as well as depicting the political developments of the time and the relationship between religion and secularism.